2017
DOI: 10.1111/gcb.13889
|View full text |Cite
|
Sign up to set email alerts
|

Individual fitness and the effects of a changing climate on the cessation and length of the breeding period using a 34‐year study of a temperate songbird

Abstract: Studies of the phenological responses of animals to climate change typically emphasize the initiation of breeding although climatic effects on the cessation and length of the breeding period may be as or more influential of fitness. We quantified links between climate, the cessation and length of the breeding period, and individual survival and reproduction using a 34-year study of a resident song sparrow (Melospiza melodia) population subject to dramatic variation in climate. We show that the cessation and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 62 publications
(114 reference statements)
2
15
0
Order By: Relevance
“…Our selection analyses showed that the fitness consequence of breeding phenology in multi‐brooded species was complex, and that ABS was more associated with start and end date than with duration. However, studies of other multi‐brooded bird species have reached the opposite conclusion that duration is more important than start and end date in determining ABS (Dunn & Winkler, ; Møller, ; Tarwater & Arcese, ). The inconsistency between our results and those of other multi‐brooded species may potentially be explained by differences in nest predation rates between species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our selection analyses showed that the fitness consequence of breeding phenology in multi‐brooded species was complex, and that ABS was more associated with start and end date than with duration. However, studies of other multi‐brooded bird species have reached the opposite conclusion that duration is more important than start and end date in determining ABS (Dunn & Winkler, ; Møller, ; Tarwater & Arcese, ). The inconsistency between our results and those of other multi‐brooded species may potentially be explained by differences in nest predation rates between species.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when individuals start breeding will generally be affected by weather in early spring (Møller, Fiedler, & Berthold, 2010), but when they stop is likely to be dependent on weather conditions much later in the season (Tarwater & Arcese, 2018;Weatherhead, 2005). As a result, any focus on start date alone may miss important effects of climate on end date, and hence on the overall duration of the breeding season (Mares, Doutrelant, Paquet, Spottiswoode, & Covas, 2017;Tarwater & Arcese, 2018). Determining exactly which climate variables at exactly which periods in the year are the best predictors of breeding phenology traits can therefore be a substantial challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On Mandarte, among‐year variation in local environmental conditions and population density drives considerable among‐year variation in song sparrow reproduction and survival (Arcese et al. ; Wilson and Arcese ; Tarwater and Arcese ), inducing substantial among‐cohort variation in mean lifespan and LRS (Lebigre et al. ; Wolak et al.…”
Section: Methodsmentioning
confidence: 99%
“…On Mandarte, among-year variation in local environmental conditions and population density drives considerable amongyear variation in song sparrow reproduction and survival (Arcese et al 1992;Wilson and Arcese 2003;Tarwater and Arcese 2018), inducing substantial among-cohort variation in mean lifespan and LRS (Lebigre et al 2012;Wolak et al 2018). Total adult population size consequently varied substantially among years (arithmetic mean: 73 ± 29 SD individuals, range: 33-128, Supporting Information S1).…”
Section: Study Systemmentioning
confidence: 99%